Implementation of neutrosophic function memberships using MATLAB program - S., Broumi; D., Nagarajan; A., Bakali; M., Talea; F., Smarandache; M., Lathamaheswari; J., Kavikumar (University of New Mexico, 2019)
Membership function (MF) plays a key role for getting an output of a system and hence it influences system’s per-formance directly. Therefore choosing a MF is an essential task in fuzzy logic and neutrosophic logic as well. Uncertainty is usually represented by MFs. In this paper, a novel Matlab code is derived for trapezoidal neutrosophic function and the validity of the proposed code is proved with illustrative graphical representation